Legal aspects of the conservation and exploitation of off-shore living marine resources in Antarctica - Van Geuns, C E (Centre for Law and Society, 2024)
As a result of man's quest for fresh sources of food, there has been ever-increasing speculation as to the possible exploitation of living marine resources found in Antarctic seas. Besides finfish, there appears to be great potential in krill fisheries. Krill are small, shrimp-like crustaceans which swarm in major concentrations in Antarctic waters. Estimates of krill fisheries vary considerably from standing stocks of 125 million metric tons as much as 6 billion metric tons. It is anticipated that krill might some day furnish a super abundant new source of protein to meet the world's ever-increasing demand for food.